2017
DOI: 10.1039/c7ra07381j
|View full text |Cite
|
Sign up to set email alerts
|

Effect of xylose on the structural and physicochemical properties of peanut isolated protein based films

Abstract: Films based on xylose and peanut protein isolate (PPI) were prepared by solution casting. The effects of xylose content (1%, 2%, 5%, 10%, 20% PPI, w/w) on the structure and mechanical properties of PPIxylose (PPI-X) film were systematically investigated. The xylose-modified PPI was firstly prepared by crosslinking and modifying of peanut isolated protein with xylose. The degree of glycosylation and surface hydrophobicity significantly increased from 5.6% to 10.9% and from 130.6 to 370.0, respectively, with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Additionally, these safe and edible films were studied for the delivery of bioactive compounds [ 268 , 269 ]. Films from plant proteins are the most attractive candidates due to their environmental sustainability [ 202 ]. However, compared to synthetic films, protein-based films have lower tensile-strength, elongation, and water-resistance properties due to their hydrophilic nature [ 270 ].…”
Section: Functional Properties and Potential Applications Of Glycamentioning
confidence: 99%
“…Additionally, these safe and edible films were studied for the delivery of bioactive compounds [ 268 , 269 ]. Films from plant proteins are the most attractive candidates due to their environmental sustainability [ 202 ]. However, compared to synthetic films, protein-based films have lower tensile-strength, elongation, and water-resistance properties due to their hydrophilic nature [ 270 ].…”
Section: Functional Properties and Potential Applications Of Glycamentioning
confidence: 99%
“…Additionally, these safe and edible films were studied for the delivery of bioactive compounds [266,267]. Films from plant proteins are the most attractive candidates due to their environmental sustainability [201]. However, compared to synthetic films, protein-based films have lower tensile strength, elongation and water resistance properties due to their hydrophilic nature [268].…”
Section: Filmsmentioning
confidence: 99%
“…One safe and effective modification method for the improvement of the film properties is the glycation or cross-linking of proteins with carbohydrates [45]. A study by Liu et al [201] showed that the glycation of peanut protein isolate with xylose led to films with 77% increased tensile strength, 67% elongation increase, and a solubility decrease from 96.6% to 43.4% compared to peanut protein isolate films. These enhanced mechanical properties and water resistance could be correlated to the increased protein surface hydrophobicity and sulfhydryl group content with the addition upon glycation with xylose [201].…”
Section: Filmsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hereupon, several studies conducted to investigate the possibility, processing, optimization, and scale up of protein–carbohydrate films as suitable alternatives for petrol‐based packaging materials. Soy protein–agar (Tian, Xu, Yang, & Guo, ), soy protein isolate–carboxymethyl cellulose (Su et al, ), whey protein–chitosan (Kurek, Galus, & Debeaufort, ), soy protein isolate–konjac glucomannan (Wang et al, ), peanut protein isolate–gum Arabic (Li et al, ), and peanut isolate protein–xylose (Liu et al, ) are examples of protein–carbohydrate blends developed in the recent years to fabricate packaging biofilms. Hence, a broad range of proteins and polysaccharides are capable of constructing packaging film materials.…”
Section: Introductionmentioning
confidence: 99%